Auto-calibrated capacitive MEMS accelerometer - L. A. Rocha (2008)
An electronic calibration technique for capacitive MEMS accelerometers based on the measurement of pull-in voltages is described. A combination of pull-in voltages and resonance frequency measurements can be used for the estimation of processinduced variations in device dimensions from layout and deviations in material properties from nominal value, which enables auto-calibration. Measurements on fabricated devices confirm the validity of the proposed technique and electronic calibration is experimentally demonstrated.